2022
DOI: 10.3847/1538-4357/ac8c95
|View full text |Cite
|
Sign up to set email alerts
|

MHD Simulations of Dense Core Collision

Abstract: We investigated the effect of magnetic fields on the collision process between dense molecular cores. We performed three-dimensional magnetohydrodynamic simulations of collisions between two self-gravitating cores using the Enzo adaptive mesh refinement code. The core was modeled as a stable isothermal Bonnor–Ebert (BE) sphere immersed in uniform magnetic fields. Collisions were characterized by the offset parameter b, Mach number of the initial core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…As isolated cores, these simulations do not accurately reflect the relation between inner regions of the cores and inflow(s) from the larger clump scales. On the other hand, simulations considering interactions between cores can explain observations of asymmetric streamers at >1000 au scales (e.g., Kinoshita & Nakamura 2022;Yano et al 2023), like in W33A where a single spiral feature is observed. Therefore, whether the streamers in G336.01-0.82 originated from gravitational instabilities, large-scale inflows and/or interaction with other cores remain unclear.…”
Section: Infall Along Streamersmentioning
confidence: 97%
“…As isolated cores, these simulations do not accurately reflect the relation between inner regions of the cores and inflow(s) from the larger clump scales. On the other hand, simulations considering interactions between cores can explain observations of asymmetric streamers at >1000 au scales (e.g., Kinoshita & Nakamura 2022;Yano et al 2023), like in W33A where a single spiral feature is observed. Therefore, whether the streamers in G336.01-0.82 originated from gravitational instabilities, large-scale inflows and/or interaction with other cores remain unclear.…”
Section: Infall Along Streamersmentioning
confidence: 97%
“…The numerical code is essentially the same as that of Kinoshita & Nakamura (2022). We use the numerical code Enzo 4 , an MHD adaptive mesh refinement (AMR) code (Bryan et al 2014).…”
Section: Numerical Codementioning
confidence: 99%
“…The phenomenon of core collision and merging has been shown to generate asymmetric structures (Kuffmeier et al 2021;Hanawa et al 2022;Kinoshita & Nakamura 2022). Recent simulations have further demonstrated that core collisions can explain several characteristics that are challenging to account for solely with the isolated core collapse model.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is crucial to investigate the processes and resulting structures that emerge during core collisions. Kinoshita & Nakamura (2022) conducted magnetohydrodynamic simulations to study the collision of two equally massive, gravitationally stable prestellar cores. Their work illustrated that core collisions lead to the formation of single or multiple protostars.…”
Section: Introductionmentioning
confidence: 99%